Pendampingan Komunikasi Bahasa Inggris dalam Pemasaran Hasil UMKM di Dusun Pamulung, Kabupaten Sumbawa - Umar Umar; Supriadin (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This program aims to provide experience, information and new knowledge related to the use of basic English during marketing results by the Gita Tambora Tourism Ambassador UMKM sector group, in Dusun Pamulung. The institutions participating in the community service activities are the Kencana Beach Cottages Travel Agency, the Postgraduate School of the Sumbawa University of Technology (UTS), the Sumbawa Islamic College (STAIS), and the UMKM Group Gita Tambora Tourism Ambassador with assistance for a certain period. The activity was carried out 5 February 2023, 24 February 2023 and 10 March 2023. There were five stages, namely; 1) survey activities; 2) interviewing; 3) setting up the sales area; 4) providing basic English communication; and 5) getting ready to serve guests. The results of these activities are: 1) travel agencies gain the trust of the tourism market; 2) Lecturers and students can implement their knowledge and experience; and 3) MSME groups can increase new knowledge regarding how to communicate using basic English with foreign guests. In addition, it will be increasing the economic value from sales suvenirs they sell.